Economic and environmental sustainability of submerged anaerobic MBR-based (AnMBR-based) technology as compared to aerobic-based technologies for moderate-/high-loaded urban wastewater treatment. (15th January 2016) - Pretel, R.; Robles, A.; Ruano, M.V.; Seco, A.; Ferrer, J.
Abstract: The objective of this study was to assess the economic and environmental sustainability of submerged anaerobic membrane bioreactors (AnMBRs) in comparison with aerobic-based technologies for moderate-/high-loaded urban wastewater (UWW) treatment. To this aim, a combined approach of steady-state performance modelling, life cycle analysis (LCA) and life cycle costing (LCC) was used, in which AnMBR (coupled with an aerobic-based post-treatment) was compared to aerobic membrane bioreactor (AeMBR) and conventional activated sludge (CAS). AnMBR with CAS-based post-treatment for nutrient removal was identified as a sustainable option for moderate-/high-loaded UWW treatment: low energy consumption and reduced sludge production could be obtained at given operating conditions. In addition, significant reductions can be achieved in different aspects of environmental impact (global warming potential (GWP), abiotic depletion, acidification, etc.) and LCC over existing UWW treatment technologies. Highlights: AnMBR was environmentally and economically compared to alternative aerobic systems. AnMBR was coupled to an aerobic-based post-treatment for nutrient removal. The minimum energy consumption in AnMBR resulted in 0.04 kWh per m 3 . Life cycle cost in AnMBR resulted in low values: €0.135 per m 3 . Significant environmental impact reductions were achieved in AnMBR.